ANALISIS AKUNTANSI PENGGAJIAN DAN PENGUPAHAN KARYAWAN PADA PT. SELYCA MULIA SAMARINDA TAHUN 2014 - Titin Ruliana, Herlinawati, H.Eddy Soegiarto (EKONOMIA, 2018)
The purpose from this research is to know the implementation of accounting system of employeespayroll and wages on PT. Selyca Mulia. This researchis done on PT. Selyca Mulia, which have the employees status as permanent employees and contract employees. Data analysis is to describe accounting of employees payroll and wages that implemented by PT. SelycaMulia. Data obtained by using Field Research andLibrary Research.The result of observation explain there are a different process in given standard salary UMK based grade level work in PT. Selyca Mulia for permanent employees and contract employees.Calculation and payment salary and wages, and overtime of employees based compared between standard regulation of ministry and PT. Selyca Mulia. Given salary and wages employees of PT. SelycaMulia still in under regulation on 2014 and it can make bad impact for company and employees.